H i intensity mapping with MeerKAT: 1/f noise analysis. Issue 3 (16th December 2020) - Li, Yichao; Santos, Mario G; Grainge, Keith; Harper, Stuart; Wang, Jingying
ABSTRACT: The nature of the time correlated noise component (the 1/f noise) of single dish radio telescopes is critical to the detectability of the H i signal in intensity mapping experiments. In this paper, we present the 1/f noise properties of the MeerKAT receiver system using South Celestial Pole tracking data. We estimate both the temporal power spectrum density and the 2D power spectrum density for each of the antennas and polarizations. We apply singular value decomposition to the data set and show that, by removing the strongest components, the 1/f noise can be drastically reduced, indicating that it is highly correlated in frequency. With two-mode subtraction, the knee frequency over a 20 MHz averaging is about 3× 10^-3 Hz, indicating that the system induced 1/f-type variations are well under the thermal noise fluctuations over a few hundred seconds time-scales. We also show that such cleaning on the time ordered data has very little impact on the 21-cm signal itself. The 2D power spectrum shows that the 1/f-type variations are restricted to a small region in the time–frequency space, either with long-wavelength correlations in frequency or in time. This gives a wide range of cosmological scales where the H i signal can be measured without further need to calibrate the gain time fluctuations. Finally, we demonstrate that a simple power spectrum parameterization is sufficient to describe the data and provide fitting parameters for both the 1D and 2D power spectrum.